Peran Pemerintah Desa Tajurhalang Kabupaten Bogor dalam Menjaga Kerukunan Antarumat Beragama - Sarifurrohman Alfaiz (Inklusiva: Jurnal Studi Agama-Agama, 2023)
This study aims to describe and analyze the role of the Tajurhalang Village Government, Bogor Regency, in maintaining inter-religious harmony. The background of this research stems from the dynamics of inter-religious relations in Indonesia, which are often characterized by conflict. As the closest government unit to the community, the village government has a strategic role in creating social harmony amid religious diversity. Therefore, this research seeks to understand the steps taken by the Tajurhalang Village Government in maintaining and strengthening inter-religious tolerance. This research uses a qualitative method with a sociology of religion approach. Data were collected through direct observation, interviews with the village government and religious leaders, and the study of related literature. This approach allowed the researcher to explore in depth the strategies applied in managing religious diversity at the village level and identify the factors that support the effectiveness of the policy. The results show that the Tajurhalang Village Government is active in maintaining inter-religious harmony through various strategies. Some of these include organizing social activities such as gotong royong, free medical treatment, and compensation for orphans, as well as fostering youth based on religious moderation. In addition, the village government initiated quarterly meetings with religious leaders, managed the allocation and limitation of houses of worship, and encouraged interfaith dialog. These efforts are supported by the utilization of local social and cultural conditions, thus creating a harmonious atmosphere in the community. Thus, Tajurhalang Village can serve as an example for other regions in managing religious diversity